Analisa Pengetahuan Dan Peran Kader Dalam Pencegahan Hipertensi Di Desa Sidorejo - wahyuni, wahyuni; Mulyaningsih; Dewi Noor Ratri, Erika; Puteri Santika, Aprilia (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) ITS PKU Muhammadiyah Surakarta, 2025)
Background: Hypertension is an increase in systolic blood pressure of more than or equal to 140 mmHg and diastolic of more than or equal to 90 mmHg. The impact of continuous high blood pressure conditions where it can cause a person's heart to work harder, so that it can cause damage to blood vessels, heart, kidneys, brain, and eyes. Therefore, hypertension must receive attention from all levels of society because it requires comprehensive and integrated long-term management efforts. Based on the identification of knowledge and the role of cadres, they do not yet know about preventing hypertension. This is because cadres have never received education/counseling about hypertension. Purpose of the study: to analyze the knowledge and role of cadres in preventing hypertension in Sidorejo Village Research method: The type of research used in this study is quantitative descriptive with a cross-sectional method approach to identify hypertension control. In this study, all populations were used as samples so that the number of samples was 30 cadres who met the inclusion criteria. The variables in this study were the knowledge and role of posyandu cadres. Results: There is a relationship between the role of Posyandu cadres and the prevention of hypertension with a Chi square result value of 0.007 and a relationship between the knowledge of Posyandu cadres and the prevention of hypertension obtained with a Chi square test result of 0.019.